Rhabdomyosarcoma Involving the Left Atrium and the Mitral Valve - Hamza A. Abdul-Hafez, MD; Ahmad K. Darwazah, MD, FRCS; Hasan Alkhatib, MD; Baraa J. Ibrahim, MD; Mahmoud Mansour, MD; Nour Dibas, MD (Texas Heart Institute Journal)
Rhabdomyosarcoma represents almost 20% of all primary malignant neoplasms of the heart. In the majority of cases, the tumor arises from the ventricular wall, although these tumors can also arise from the atrial walls and mimic atrioventricular valve stenosis. This report presents a case of a patient diagnosed with an atrial mass that was detected by transthoracic echocardiography and confirmed by histopathology. The mass was successfully resected during an uneventful surgical intervention, but the patient died 6 months after the procedure.